Effects of Alkali Metallization on the Luminescence Degradation of Porous Silicon - Özer, Mehmet; Kayahan, Ersin; Oral, Zehra Banu (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2012)
In this study, change in the intensity and stability of photoluminescence obtained by porous silicon were investigated with illumination time and metallization state. The porous silicon samples were metallized by immersing into solutions containing 3 mM LiNO3, KNO3 and NaNO3 metal salts using immersing plating method. The surface bond configurations of porous silicon were monitored by the Fourier transmission infrared spectroscopy and the results showed that the surfaces of the samples were oxidized after the metallization. The photoluminescence intensity increased after certain critical immersion times and photoluminescence spectrum shifted towards the high energy region after the metallization. Photoluminescence intensity of metallized porous silicon samples was more stable than as-anodized porous silicon samples. The experimental results suggested the possibility that oxygen and/or alkali metal (Li, K and Na) passivation of porous silicon surface could be a suitable way to obtain an efficient and stabilized photoluminescence.
Keywords: Photoluminescence; Fotolüminesans